Assessment of Swacchta Guidelines Implementation at Government District Teaching Hospital, Madikeri, Kodagu District, Karnataka State using KAYAKALP Assessment Tool - Shivaraj B Mallappa; Parvathy T Somaiah (Medsci Publications, 2016)
Introduction: Cleanliness and hygiene is crucial for healthcare settings. The Swachh Bharat Abhiyaan is a national campaign initiated by the Government of India to promote cleanliness in public spaces. 'KAYAKALP' is the program to promote cleanliness and enhance the quality of public health facilities. Objectives: To assess the swachta guidelines implementation at government district hospital, Kodagu, Karnataka state using Kayakalp assessment tool. Methods: A cross sectional study was conducted at District hospital in Madikeri, Karnataka state. The assessment tool used for this study was the standard national assessment tool- score card- Swachhta Guidelines for Public Health Facilities provided by the Ministry of Health & Family Welfare Government of India (MOHFW, 2015). Results: The total score was 232 out of 500 which came to 46.4%. The following sub topics got the respective scores depicted in the bracket: Hospital upkeep (35%), Sanitation & hygiene (53%), biomedical waste management (57%), Infection control (50%) Support Services (48%) and Hygiene promotion (26%). Conclusion: The initial assessment results at the district hospital showed poor results. There is an urgent need to improve the standards in all sections of the facility to give good care to the public.